Methods for Developing Students' Mathematical Thinking Skills in Schools - Sanobar Ibragimovna Kenjayeva, (Zien Journals, 2023)
This article will focus on methods of developing students' mathematical thinking skills. At the same time, attention to the field of education, about types of thinking and questions that enhance mathematical thinking are also briefly covered.
Keywords: education; thinking; mathematics; school